Light emitting diode (LED) use in artificial lighting for broiler chicken production - Santana, Mayara R. de [UNESP]; Garcia, Rodrigo G.; Naas, Irenilza de A.; Paz, Ibiara Correia de Lima Almeida [UNESP]; Caldara, Fabiana R.; Barreto, Bruna (Associação Brasileira de Engenharia Agrícola, 2014)
Light emitting diode (LED) has been used in commercial poultry industry by presenting superior energy savings and providing feasibility on production process. The objective of this research was to evaluate performance and carcass yield of broiler chickens exposed to different LED colors compared with fluorescent lamps. For that, two experiments (E1 and E2) were performed and 2,646 Cobb® chickens were used. In experiment E1, male birds were exposed to 20 lux artificial lighting with red, yellow, blue, and white LED bulbs; and fluorescent bulb. In experiment E2, male and female birds were exposed to 15 lux artificial lighting with red and blue LED bulbs; and fluorescent bulb. Cumulative weight gain (kg), feed intake (kg), feed conversion, hot carcass weight (kg), carcass yield (%), and breast and thigh + drumstick yield (%) were used as response variables. Results showed no difference (p > 0.05) among treatments for performance, carcass yield, and cut yield in experiment E1. In experiment E2 there was only difference between genders (p < 0.05) and males showed higher total weight gain, feed intake, hot carcass weight and thigh + drumstick yield. Different LED color use had same effect as fluorescent lights on broiler performance and carcass yield.

A utilização de lâmpadas de diodo emissor de luz (LED) tem-se destacado na avicultura por apresentar economia de energia e proporcionar viabilidade do processo de criação. O objetivo desta pesquisa foi avaliar o desempenho e o rendimento de carcaça de frangos de corte expostos a diferentes cores de LED, em comparação às lâmpadas fluorescentes. Para isso, foram realizados dois experimentos (E1 e E2) utilizando 2.646 aves da linhagem Cobb®, em que, no experimento E1, as aves (machos) foram expostas à iluminação artificial (20 lux) com LED vermelho, amarelo, azul, branco e lâmpada fluorescente, e no experimento E2, as aves (machos e fêmeas) foram expostas à iluminação artificial (15 lux) com LED vermelho e azul, e lâmpada fluorescente. Como variáveis respostas, foram medidos o ganho de peso acumulado (kg), o consumo de ração (kg), a conversão alimentar, o peso de carcaça quente (kg), o rendimento de carcaça (%) e de peito, e a coxa-sobrecoxa (%). Os resultados mostraram que não houve diferença (p > 0,05) entre os tratamentos para desempenho e rendimento de carcaça e cortes, no experimento E1. No experimento E2, houve diferença apenas entre os sexos (p < 0,05), com machos apresentando maior ganho de peso acumulado, maior consumo de ração, maior peso de carcaça quente e maior rendimento de coxa-sobrecoxa. Pode-se concluir que a utilização de LED, nas diferentes cores, apresentou o mesmo efeito das lâmpadas fluorescentes sobre o desempenho e o rendimento de carcaça de frangos de corte.
Diodo emissor de luz (LED) na iluminação artificial de frangos de corte
Keywords: poultry; production; artificial lighting; LED; avicultura; produção; iluminação artificial